Evaluation of lung ventilation in relation to the waist/hip ratio among healthy adults. - Ahmed, Amjad F.; Al Amin, Afraa M-; Ayoob, Mahdi S (Journal of the Faculty of Medicine Baghdad, 2012)
Background: lung function is closely related to anthropometric variables. Anegative relationship between different adiposity markers and lung function has been well established.